2015
DOI: 10.1117/1.jrs.9.096038
|View full text |Cite
|
Sign up to set email alerts
|

Optical remote sensing of sound in the ocean

Abstract: Abstract. We propose a remote sensing technique to measure sound in the upper ocean. The objective is a system that can be flown on an aircraft. Conventional acoustic sensors are ineffective in this application, because almost none (∼0.1%) of the sound in the ocean is transmitted through the water/air interface. The technique is based on the acoustic modulation of naturally occurring bubbles near the sea surface. It is clear from the ideal gas law that the volume of a bubble will decrease if the pressure is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This pressure can be amplified in shallow water, such as lagoons [4,177]. Churnside et al, 2014 [176] suggested theoretical approaches that use ARS images (i.e., LiDAR) to measure sound in the upper ocean by modelling natural bubbles near the sea surface. Soares et al, 2019 [177] used the RS approach based on SS hydrophone (called digitalHyd SR-1) to record the noise between summer and winter in the Ria Formosa lagoon in Portugal.…”
Section: Underwater Noisementioning
confidence: 99%
“…This pressure can be amplified in shallow water, such as lagoons [4,177]. Churnside et al, 2014 [176] suggested theoretical approaches that use ARS images (i.e., LiDAR) to measure sound in the upper ocean by modelling natural bubbles near the sea surface. Soares et al, 2019 [177] used the RS approach based on SS hydrophone (called digitalHyd SR-1) to record the noise between summer and winter in the Ria Formosa lagoon in Portugal.…”
Section: Underwater Noisementioning
confidence: 99%
“…The analysis of lidar returns from photon counting systems is, in many ways, similar to analysis using analog systems (E.g. Churnside, Naugolnykh, and Marchbanks, 2014;Guenther, 1985;Guenther, LaRocque, and Lillycrop, 1994). A principal difference is that, instead of analyzing a full waveform return from a single pixel illuminated by a high energy analog pulse, an equivalent, but not identical, histogram must first be generated from along track returns.…”
Section: Introductionmentioning
confidence: 99%